Causes and Strategies for Mitigating Farmer–Herder Conflicts in Northern Taraba State - Sinjen Peter Monday (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study examined the economic and environmental dynamics of farmer–herder conflicts in Northern Taraba State, Nigeria, with a view to identifying the major causes of the conflicts, assessing their economic consequences, and determining appropriate mitigation strategies. The study adopted a descriptive survey research design. The population comprised farmers, herders, community leaders, and other relevant stakeholders in selected Local Government Areas of Northern Taraba State. A sample size of 400 respondents was selected using a multistage sampling technique, while 390 completed questionnaires were retrieved and used for the analysis, representing a response rate of 97.5%. Data were collected using a structured questionnaire and analyzed using frequency, percentage, mean, standard deviation, Pearson Product Moment Correlation, and simple linear regression at a 0.05 level of significance. The findings revealed that shrinking grazing land, competition over land, water scarcity, climate change, and population increase were the major causes of farmer–herder conflicts. The study further established that the conflicts have significant economic consequences, including reduced farming activities, loss of income, displacement of residents, destruction of infrastructure, and reduced trade. Hypotheses tested showed a significant positive relationship between environmental scarcity and farmer–herder conflicts, while resource competition significantly predicted the occurrence of the conflicts. Furthermore, government intervention, improved security, community dialogue, ranching, and the revival of grazing routes were identified as effective strategies for mitigating the conflicts. The study concluded that environmental scarcity and competition over natural resources remain the principal drivers of farmer–herder conflicts in Northern Taraba State. It recommended the implementation of sustainable land-use policies, modern ranching systems, strengthened security measures, and inclusive community-based conflict resolution mechanisms to promote peaceful coexistence, improve agricultural productivity, and foster sustainable socio-economic development in the study area.